PENGARUH MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA VIDEO PEMBELAJARAN TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS V SDN TAMBAHMULYO 01 - Ahmad Mujibburrohman (COLLASE (Creative of Learning Students Elementary Education), 2023)
This study aims to analyze the effect of the Problem Based Learning (PBL) learning model assisted by learning video media on understanding mathematical concepts. The research method used in this study is a quantitative method in the form of Quasy Experimental Design (pseudo-experimental). The design used in this study was a nonrandomized pretest-posttest control group design. The sample of this study was class V SD Tambahmulyo 01, namely class VA and VC. The data collection technique was test and non-test, the test technique used understanding of mathematical concepts while the non-test technique used observation and documentation. Data analysis techniques using normality test, homogeneity, and t test. The results of data analysis concluded that there was an influence of the PBL learning model assisted by video learning media on the ability to understand mathematical concepts of fifth grade students at SDN Tambahmulyo 01. This is evident from the results of the paired sample t-test, the results obtained were 0.03 <0.05 meaning H0 was rejected, meaning that the PBL model assisted by learning video media has an effect on the understanding of mathematical concepts of fifth grade students at SDN Tambahmulyo 01.Keywords: PBL Model, Understanding Mathematical Concepts, Learning Videos